DNA Methylation Biomarkers in Stool Samples: Enhancing Colorectal Cancer Screening Strategies - Porcaro, Floriana; Voccola, Serena; Cardinale, Gaetano; Porcaro, Piercarmine; Vito, Pasquale (Oncology Reviews, 2024)
Colorectal cancer (CRC) is a significant global health challenge, ranking among the leading causes of cancer-related mortality worldwide. Despite efforts in prevention and early detection, CRC incidence and mortality rates are expected to rise substantially. Traditional screening methods like gFOBT, FIT, flexible sigmoidoscopy, colonoscopy, CTC, and colon capsule have limitations, including false positives/negatives, limited scope, or invasiveness. Recent developments in CRC screening involve DNA methylation biomarkers, showing promise in detecting early-stage CRC and precancerous lesions. Stool-based DNA testing is emerging as a noninvasive and convenient method for detecting CRC-associated DNA methylation alterations, offering potential for earlier detection compared to traditional methods. Several commercial stool-based DNA methylation tests targeting different genes associated with CRC have demonstrated varying sensitivity and specificity, some surpassing traditional screening methods. Challenges remain in optimizing their performance and accessibility. This review discusses how DNA methylation biomarkers could enhance CRC screening, and stool-based DNA methylation tests could revolutionize CRC screening practices, comparing them to the gold standard.